Reforming the Role of Judges in Assessing Evidence Authenticity and Legality: A Comparative Study Using the Exclusionary Rule Approach - Rustamaji, Muhammad; Sitompul, Shalih Mangara; Khoiruddin, Aldi Rizki (Universitas Airlangga, 2026)
The renewal of the role of judges in the authentication and examination of evidence has become crucial in line with the complexity of electronic evidence and the demands for the protection of human rights in criminal proceedings. A comparative study of the legal systems of the US (Miranda Rules), the UK (Judges' Rules), and the Netherlands (Wet Elektronisch Procesdossier) reveals disparities in the mechanisms for excluding illegal evidence. In the Indonesian context, through the Criminal Procedure Code Bill (Articles 222-228), efforts are being made to adopt the exclusionary rule in a limited manner by affirming the authority of judges to assess the authenticity and legality of evidence acquisition (bewijs voering). This normative legal research uses a comparative law approach and deductive syllogistic analysis to construct an enhancement of judges' technical capacity in verifying metadata, digital evidence integrity, and applying digital forensic standards in line with developments in Singapore's Electronic Transactions Act and Malaysia's Electronic Evidence Act. The findings of the study indicate that reform of the evidence system in Indonesia requires synergistic harmonization between the expansion of judicial authority as stipulated in Article 222(4) and (5) of the Draft Criminal Procedure Code and the strengthening of judges' technical digital competencies. These provisions grant judges the authority to actively assess the authenticity and legality of evidence acquisition, including electronic evidence, which requires a deep understanding of technical aspects such as metadata, data integrity, and digital forensic procedures. However, without this technical capacity enhancement, the expansion of judicial authority risks being ineffective and may even lead to wrongful convictions, which contradicts the principles of the due process model. Therefore, this harmonization must not only address normative and legal aspects but also practical implementation through intensive training for judges in information technology and digital forensics, as well as the provision of supporting facilities in courts. This approach aligns with practices in modern jurisdictions such as the United States and Singapore, which integrate the exclusionary rule with high technical standards to ensure procedural justice and optimal protection of defendants' rights. Thus, this reform is expected to strengthen the credibility of the Indonesian judiciary in facing the challenges of the digital age and prevent the misuse of evidence that could undermine substantive justice.